Guinea-Bissau : Use of Fund Resources -Request for Emergency Post-Conflict Assistance; Staff Report; Press Release; and Statement by the Executive Director for Guinea-Bissau. (IMF Staff Country Reports; Country Report ;, 2008)
Guinea-Bissau remains fragile, after nearly a decade of conflict and political instability. Fiscal performance has improved markedly since the new government implemented its emergency fiscal plan. The focus of the government on stabilizing public finances and improving economic management and transparency reflects a sound view of urgent priorities. Efforts to enhance revenue collection, including improving tax administration, are necessary to boost revenues on a lasting basis and ensure that the state has the resources to meet its core expenditure needs and provide basic public services.